Pembangunan Jalan Lingkar Utara dan Perubahan Bentuk dan Struktur Ruang Kota Magetan - Setiono, Dwi Cahyo (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2016)
Magetan Regency Government built north-ring-road in order to alleviate traffic congestion in urban center area. However, the ring-road attracted people to utilize the surrounding area. The area utilization was estimated influencing the form and the structure of Magetan Urban Area. In this respect, this research is aimed to explain the relationship between north-ring road development and the change of form and spatial structure of Magetan Urban Area by using a quantitative approach and a descriptive method in its practice. As the result, the form of Magetan Urban area is compact-square with linear form in the several parts of the urban area. The structure of Magetan Urban Area is sectoral which characterized by the main activity in urban center and swept away following the main road. The development in the periphery area was caused by the increase of activities in urban center. However, the development did not change the urban form, but it contributed to the larger size of the urban form. The development of north-ring road only impacted to the development in the several villages surrounded the road, so it did not change the form and the structure of Magetan Urban Area directly.